(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
The paper examines the effectiveness of materials designed and distributed among course instructors to teach an Intermediate Composition course in an online platform. The study has been established in the context of a private university in Bangladesh, where the students enrolled are bi-lingual learners. The paper visits literature in fields of technology-enhanced language learning (TELL), Activity theory and Scaffolding to understand the extent to which the teaching materials are effective. In addition, through means of a semi-structured interview responses from course instructors, the paper highlights numerous strengths, weaknesses and suggestions regarding the materials disbursed among the faculty members. The research findings suggest that the given materials were useful and helped to promote understanding of course content, but improvements can be made to assist student learning. Increased emphasis on learner autonomy can facilitate the learning process for students and motivate them to become independent learners.